Gross Anatomical Study of Nasal Cavity in Turkey(Meleagris gallopavo) - Dharani, P; Kumaravel , A (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was aimed to document the gross anatomical features of nasal cavity in Turkey. Six heads from healthy birds were utilized for this study. The nasal cavity started with elliptical external nares and divided completely into two equal halves by a cartilaginous nasal septum. Each half of the cavity was triangular/cone shaped which lodged rostral, middle and caudal nasal conchae. The middle nasal concha was largest and situated in an oblique manner. The caudal concha was smallest and bulla-like. Five nasal meatuses were noticed in the nasal cavity of Turkey.